Journey to the East: Jūnikai, Japan’s first skyscraper - Alfaro Lera, José Antonio (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2022)
One century after the Great Kanto Earthquake devastated Tokyo and Yokohama in September 1, 1923, the remains of the foundation of the Jūnikai (Twelve-Stories), or Ryōunkaku (Cloud-Surpassing Tower), the first Skycraper of Japan, have been discovered in the old Asakusa Park, in Tokyo. It was designed by the Scottish sanitary engineer William Kinnimond Burton (1856-1899), and inaugurated in 1890. Contemporary of Adler and Sullivan’s first high-rise buildings in Chicago, it was the icon of the Asakusa Park, a copy in Japan of the cheerful western entertainment districts such as Broadway or Montmartre. The Ryōunkaku was the focus of several pages of Japanese modernist literature and its powerful presence in Tokyo’s skyline made it one of the symbols of the country’s opening to the west, which started with the Meiji Restoration, a time of transformations in which domestic intimacy moved from the strict horizontality of Japanese dwellings—embodied by the delicate platforms built to observe the moon in the town of Katsura—to the vertiginous verticality of the new forms of high-rise living of modern towers.